Environmental Factors Associated with Incidence of Stunting in Toddlers: Literature Review - Ilmy Nur Amalia; Onny Setiani; Yusniar Hanani Darundati (Fakultas Teknik, 2023)
Stunting is a public health problem that receives special attention because it is related to human resources in the future. Many studies state that stunting is related to nutritional problems in toddlers, only a few studies show that environmental factors are an indirect cause of stunting in toddlers. The purpose of this systematic study was to describe the relationship between environmental factors and the incidence of stunting in toddlers. This literature study used a scoping review method by searching through several search engines such as Scopus and nature and science direct databases supported by Diponegoro University. The articles selected for review are articles that contain the results of observational studies (cross-sectional, cohort and case control) that analyze environmental factors with the incidence of stunting in toddlers. From 7 articles, only 1 study stated that environmental factors did not affect the incidence of stunting, 6 other articles stated that environmental factors were an indirect cause of stunting in toddlers. Environmental factors related to stunting are the source of drinking water, the practice of haphazard defecation, the presence of animal waste in the living environment, environmental enteric dysfunction, the availability of proper toilet, the practice of washing hands with soap when feeding children, exposure to cigarette smoke, exposure to PM 2.5, household waste and clean and healthy living behavior.